La educación en el período del Rig-Veda: enseñanzas que se desprenden - Puig, Pedro Font (Revista Española de Pedagogía, 2025)
Hindu culture deserves special attention from the pedagogues, both by its historical value and by the practical consequences that we may obtain and that are interesting. Based in the Rig-Veda, Rik-Prãtizãkya, Upanishads... Doctor Font y Puig emphasizes the utility of the cultivation of fancy to form the ability of high and deep intuitions besides the utility of the cultivation of sentiment. But he points out the difficulties shown by hindu life owing to the exclusiveness of the education of fancy and sentiment in the intelectual and volitional orders as such: lack of logic continuity, inaccuracy in the ideas, carelessness in the contradictions... lack of voluntary inhibition, lack of initiative..